Analisis Fungsi Alokasi Keuangan Daerah (Studi pada bidang Pendidikan dan Kesehatan di Propinsi Banten) - Ismanto Ismanto (Jurnal Administrasi Publik, 2013)
Policy mismatch is the relevant term to describe the inconsistence between problems met by the people and financial policy being chosen. Improper quality of public services especially in health and education did not correlate significantly with the provincial financial policy. The problem of accessibility and service quality in both fields is not progressively getting better. Although the amount of annual government’s expenditure in both field always increase, the percentage is getting reduced yearly. As the result, the financial allocation function did not effectively work to overcome those problems. And finally, as public goods, the availability and accessibility of health and education services can not prevalently being consumed by the people.